Somatosensation in OA: exploring the relationships of pain sensitization, vibratory perception and spontaneous pain - Anisha B. Dua (BMC Musculoskeletal Disorders, 2018)
Abstract Background Pain in osteoarthritis (OA) remains poorly understood. Different types of somatosensory alterations exist in OA including hyperesthesia and increased sensitivity to painful stimuli as well as those of decreased sensitivity to cutaneous stimuli including vibratory perception threshold. The relationship between these different somatosensory measures has not been previously evaluated in OA. In this observational study, we evaluated relationships between vibratory perception (VPT), pressure pain detection thresholds (PPT), allodynia and subjective pain in knee OA. Methods Forty-two persons with moderate to severe knee OA and 12 controls without OA were evaluated. VPT was measured using a biothesiometer. Allodynia was measured by application of a 60 g Von Frey monofilament repeatedly to predetermined sites. PPTs were measured using a pressure algometer. Results Increased vibratory acuity was associated with lower PPTs and presence of allodynia. Allodynia was more common in OA than controls (54.8% vs 16.6%, p = 0.024 in the ipsilateral knee, and 42.9% vs 0%, p = 0.005 in the contralateral knee). OA participants with allodynia had lower PPTs than those without allodynia. In those with OA, spontaneous knee pain was associated with lower PPTs and with allodynia. Conclusion This study confirms the presence of somatosensory alterations in OA. Sensory alterations (vibratory perception) were shown to be related to nociceptive alterations (sensitization) in OA, showing a general increased sensitivity to cutaneous mechanical stimulation. Understanding these relationships is an important step in delineating the complicated pathophysiology of pain processing in OA.